2020
DOI: 10.1111/tran.12424
|View full text |Cite
|
Sign up to set email alerts
|

Walking with light and the discontinuous experience of urban change

Abstract: This paper is concerned with the affective power of light, darkness, and illumination and their role in exposing and obscuring processes of rapid urban change. Little academic attention has focused on how lighting informs multiple, overlapping, and intersecting urban temporalities and mediates our experience of an ever-changing city. This paper foregrounds a walk through the illuminated city at night as an epistemic opportunity to develop an embodied account of material and temporal change in ways that disrupt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 48 publications
(70 reference statements)
0
12
0
Order By: Relevance
“…As night studies has grown, the value of this approach is being shown over an increasing number of areas. For example, there is a growing literature on nocturnal mobilities which ties together work on darkness, fear and nightlife, and which shows some of the insights that can be created by bringing these themes together (Cook and Edensor, 2017; Ebbensgaard and Edensor, 2021; Farina et al, 2021; Duff and Moore, 2015; Smeds et al, 2020; Wilkinson and Wilkinson, 2018). Across this research, by turning attention to the nocturnality of nocturnal mobility researchers have found new insights and new phenomena that might otherwise have been overlooked.…”
Section: Night Studies and Geographymentioning
confidence: 99%
“…As night studies has grown, the value of this approach is being shown over an increasing number of areas. For example, there is a growing literature on nocturnal mobilities which ties together work on darkness, fear and nightlife, and which shows some of the insights that can be created by bringing these themes together (Cook and Edensor, 2017; Ebbensgaard and Edensor, 2021; Farina et al, 2021; Duff and Moore, 2015; Smeds et al, 2020; Wilkinson and Wilkinson, 2018). Across this research, by turning attention to the nocturnality of nocturnal mobility researchers have found new insights and new phenomena that might otherwise have been overlooked.…”
Section: Night Studies and Geographymentioning
confidence: 99%
“…The art of storytelling or narration starts with light at its center, where communal activities surround it, suggesting that our life, values, and needs intersect heavily with light and its capacity for us to create narration (Hough, 1932). One extreme example of this was the notorious Nazi regime at Nuremberg to use light as a propaganda tool for self-grandeur perception while twisting its meaning as "cathedrals of light" with 130 giant searchlights (Ebbensgaard & Edensor, 2021). The evolution of this storytelling with light can be found in West Sumba, Indonesia, in the form of fired-up football (Figure 1).…”
Section: From Perception To Narrationmentioning
confidence: 99%
“…Urban community spaces are significantly different spaces at night and during the day; they assemble in different ways depending on, for example, light/dark, open/ closure of businesses, busy/quiet roads and pedestrian spaces. A key element of the night time assemblage is the visual aspectthe lighting (Laing Ebensgaard and Edensor, 2021;Shaw, 2014) because a sense of community implies to many a sense of safety created through lighting (Shaw, 2014). It is the material infrastructure that makes these lights possible (Klinenberg, 2018).…”
Section: The Materials Sociality Of Lightmentioning
confidence: 99%